Finite element analysis of reinforced concrete beam under dynamic loading / Mariati Sulaiman - Sulaiman, Mariati (Faculty of Civil Engineering, 2005)
Reinforced concrete has developed into the most widely used material for civil engineering and large building structures over a period of 100 years. Its popularity stems from its architectural flexibility, the ready availability of its constituent material in most parts of the world, and consequent economy Reinforced concrete beam is defined as a structural member whose cross sectional dimension is relatively smaller than its length. Beams are commonly subject to transverse loading, which is a type of loading that creates bending in beam. In this study, reinforced concrete beam will be analyzed by using Finite Element Method. The model analyzed of beam sizes at 125 x 150 x 1400 mm (width, height, length respectively) LUSAS 13.5 Software will be adopted to create finite element model. The model will be modeled using 3D space (x, y, and z). The dynamic load will be subjected to the beam. The software will be used to develop variations for the model plots of deformed mesh, displacement, stress and strain contours.